RASO: an Ontology on Requirements for the Development of Adaptive Systems. - Peçanha, Cássio Capucho; Duarte, Bruno Borlini; Falbo, Ricardo de Almeida; Souza, Vitor E. Silva (Cadernos do IME - Série Informática, 2019)
There is growing interest in software that can adapt their behavior to deal with deviations between their outcome and their requirements at runtime. A systematic mapping of the literature on self-adaptation approaches based on requirements models revealed over 200 papers on this subject. However, there is still a lack of a formal and explicit representation of the concepts in this domain, which can lead to problems in communication, learning, problem-solving and interoperability. To make a clear and precise description of this domain, this paper proposes RASO: the Requirements-based Adaptive Systems Ontology. RASO was built using a well-established Ontology Engineering method, is grounded on a foundational ontology and reuses concepts from other software-related ontologies. The ontology was evaluated by mapping constructs from the most referenced approaches from the literature to its concepts, thus creating a path for interoperability among them.